2007
DOI: 10.1002/hed.20672
|View full text |Cite
|
Sign up to set email alerts
|

Swallowing disorders in the first year after radiation and chemoradiation

Abstract: Background-Radiation alone or concurrent chemoradiation can result in severe swallowing disorders. This manuscript defines the swallowing disorders occurring at pretreatment and 3 and 12 months after completion of radiation or chemoradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
170
1
2

Year Published

2011
2011
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 186 publications
(192 citation statements)
references
References 12 publications
19
170
1
2
Order By: Relevance
“…Persistent deficits in swallowing physiology occurred in four physiological parameters from 4-6 weeks to 6 months post-treatment, indicating that if there was no improvement in the period immediately following treatment, participants experienced impairment in that parameter for at least 6 months post-treatment, similar to findings in the chemoradiation literature 15,36,37 . Impairments of palatal closure, position of the bolus at the onset of the swallow, and laryngeal excursion have been found in the early post-treatment phase in chemoradiation patients with little functional improvement by 12 months post-treatment 30, 58, 60 , and findings from the current study may suggest AFRT-CB causes similar long-term functional impairment.…”
Section: Six Months Post-treatmentsupporting
confidence: 66%
See 2 more Smart Citations
“…Persistent deficits in swallowing physiology occurred in four physiological parameters from 4-6 weeks to 6 months post-treatment, indicating that if there was no improvement in the period immediately following treatment, participants experienced impairment in that parameter for at least 6 months post-treatment, similar to findings in the chemoradiation literature 15,36,37 . Impairments of palatal closure, position of the bolus at the onset of the swallow, and laryngeal excursion have been found in the early post-treatment phase in chemoradiation patients with little functional improvement by 12 months post-treatment 30, 58, 60 , and findings from the current study may suggest AFRT-CB causes similar long-term functional impairment.…”
Section: Six Months Post-treatmentsupporting
confidence: 66%
“…There is no consensus on data reduction in VFS with some studies rating the first swallow 33 , rating the average performance across two or three swallows [34][35][36] , or giving no comment on the data analysis 37,38 . In the current study, the worst performance observed across the food and fluid trials was used for analysis.…”
Section: Swallow Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,9,[14][15][16][17] Decreased tongue mobility and strength, impairment in bolus preparation and transport, increased oral residue were described as oral phase disorders. 15,18,19 Delayed triggering swallowing reflex, impairment in velopharyngeal closure, decreased tongue base retraxion, pharyngeal contraction, hyolaryngeal elevation, airway closure, upper esophageal sphincter (UOS) opening and increased residue in tongue base, vallecula, pharynx and pyriform sinus were determined as phryngeal disorders after RT.…”
Section: Discussionmentioning
confidence: 99%
“…3 The effects of RT on mobility and strength of oropharyngeal structures were demonstrated in previous studies. [4][5][6][7][8][9][10] Optimal rehabilitation programme includes not only oropharyngeal exercises which are focus on oropharyngeal mobility and strength but also neck mobility and strengthening exercises. Although we know the importance of head and neck structures mobility and strength in swallowing rehabilitation, there is no study to evaluate the artrokinematic characteristics of head and neck like posture, range of motion, strength and endurance after RT.…”
Section: Introductionmentioning
confidence: 99%